Rancang Bangun Rekam Medis Elektronik Rawat Jalan Berbasis Web Mobile View di Puskesmas I Melaya - Ni Kadek Sri Windariyasih; Rai Riska Resty Wasita; Gerson Feoh (Universitas Malahayati Lampung, 2023)
ABSTRACT The still manual management of medical records at Puskesmas I Melaya resulted in medical records not being found, caused by the medical record storage racks being in three different places and not being kept safe. This causes the medical record search time to exceed the standard procedure. With the above problems, a web-based mobile view-based electronic medical record was designed to facilitate the search for medical records and their management in a computerized manner. The development of a web-based mobile view electronic medical record system uses the System Development Life Cycle method. Sample determination was determined by probability sampling technique with simple random sampling with 19 samples. Testing this information system uses black box testing. Tested its usability using the USE Questionnaire with 30 questions. Usability testing with the USE Questionnaire proved 81.40% results with an